A qualitative analysis of parents' perceptions of weight talk and weight teasing in the home environments of diverse low-income children. (September 2015) - Berge, Jerica M.; Trofholz, Amanda; Fong, Sherri; Blue, Laura; Neumark-Sztainer, Dianne
Highlights: Qualitative research on weight talk/teasing in diverse low-income households is limited. Parents engaged in overt and covert weight talk/teasing and weight talk contradictions. Parents reported reciprocal teasing among family members. Parents reported cultural factors relating to weight talk/teasing. Themes are tied to family-based interventions to reduce weight talk/teasing at home. Abstract: Research has shown that family weight talk and teasing are associated with child overweight status and unhealthy weight control behaviors. However, little is known about how weight talk and teasing are experienced in the home, how parents respond, and what factors influence whether weight talk and teasing occur. The main objective of this study is to qualitatively examine weight talk and teasing in the home environments of diverse low-income children. Parents ( N  = 118) from a mixed-methods cross-sectional study were interviewed in their home. The majority of parents (90% female; mean age = 35 years.) were from minority (65% African American) and low income (<$25, 000/year) households. A grounded theory analysis found the following themes: weight talk contradictions, overt and covert weight talk/teasing, reciprocal teasing, and cultural factors related to weight talk/teasing. These themes should be addressed when developing family-based interventions to reduce weight talk and teasing in the home environment.